(K, Na)NbO3‐Based Lead‐Free Piezoceramics: Fundamental Aspects, Processing Technologies, and Remaining Challenges. Issue 12 (26th November 2013) - Li, Jing‐Feng; Wang, Ke; Zhu, Fang‐Yuan; Cheng, Li‐Qian; Yao, Fang‐Zhou; Green, D. J.
<x xml:space="preserve">Abstract</x> Environment‐friendly lead‐free piezoelectric ceramics have been studied extensively in the past decade with great progress particularly in systems based on a niobate perovskite compound formulated as (K, Na)NbO3 (abbreviated as KNN). A comprehensive review on the latest development of KNN‐based piezoelectric ceramics is presented in this article, including the phase structure, property enhancement approaches, and sintering processes as well as the status of some promising applications. The phase structure of KNN was reexamined and associated with the effect of chemical modification on its tetragonal‐to‐orthorhombic transition. Then, a special focus is placed on the temperature dependence of piezoelectric properties of KNN‐based ceramics, followed by reviewing the recent approaches devoted to the temperature‐stability enhancement. The processing fundamentals related to the sintering of KNN‐based ceramics are also presented with an emphasis on compositional and microstructural control. Finally, this review introduces several industrial attempts of traditional piezoceramic products using KNN‐based ceramics and the studies on some promising application in authors' laboratory.